The Effect of Counseling on Postpartum Women's Sexual Satisfaction - Silfia, Niluh Nita; Usman, Hastuti; Dewie, Artika (Jurnal Bidan Cerdas, 2023)
Introduction: Only 7–13% of women say they need help or advice to overcome problems regarding sexual satisfaction; 40% of women do not even seek help from a doctor for their sexual complaints. Meanwhile, 54% reported that they only wanted to find a solution to the problem of sexual satisfaction without actually doing it. Purpose: to determine the effect of counseling on postpartum women's sexual satisfaction in the Puskesmas Kamonji working area. Method: The research was conducted in July–August 2023 with a one-group pretest-posttest design and a sample size of 49 women who had babies aged 2–6 months. Using the Wilcoxon consecutive sampling analysis technique. The results before being given counseling showed that 42.9% of respondents were sexually satisfied, but after being given counseling about sexual satisfaction, 57.3% of respondents felt sexually satisfied (p-value<0.001). Conclusion: There is a significant difference in sexual satisfaction before and after providing counseling about sexual satisfaction to respondents. It is recommended that health facilities provide counseling about providing for sexual needs periodically, from pregnancy to the postpartum period, and involve the roles of husband and family.